STRATEGI PENGELOLAAN HUTAN RAKYAT DI KABUPATEN LUWU UTARA - Salma A. Kaisang; Nuraeni Nuraeni; St Subaedah (Percetakan Umi Toaha Makassar, 2020)
People forest in North Luwu regency has a large enough potential but has not been managed intensively. The purpose of this research : reviewing people forest management in North Luwu regency, identifying internal and external factors in people forest management and formulate people forest management strategies in North Luwu regency. This research was conducted in North Luwu regency with a survey method in three dictricts, the sample was taken randomly with a total of 47 respondents. Data analysis was performed using descriptive methods and SWOT analysis. The result of the analyses indicated that the strategy could be best applied was strength-opportunity (SO) strategy, namely by (1) land optimization by developing agroforestry systems to increase land productivity by planting MPTS ( Multipurpose Tree Species) plants and the same time minimizing erosion, (2) increase the institutional capacity of forest farmer groups (KTH), and (3) inventory of existing potential to regulate planting and production in order to ensure the sustainability of people forest.